The impact of heterogeneity in bilateral investment treaties on foreign direct investment - Zhaokuan Zhu; Chang-Bong Kim; Jaeeun Hwang (Journal of Applied Economics, 2025)
Prior research remains highly debated regarding whether bilateral investment treaties (BITs) effectively attract foreign direct investment (FDI). In this context, this study introduces a new dataset, the international investment agreement (IIA) mapping project, and panel data on FDI flows among 203 countries worldwide from 2009 to 2021. The findings indicate that higher BITs quality indicators, including breadth, depth, and non-economic standards (NES), significantly enhance FDI stock, with this effect remaining robust across various model specifications. Furthermore, as the domestic institutional quality of host countries improves, this positive effect is further amplified. These insights deepen the understanding of BITs effectiveness and offer policy implications for policymakers aiming to attract FDI through more comprehensive BITs.